Benefits of dancing in the self-assessment of members of a contemporary dance formation - Krysiak, Joanna (Contemporary problems of physical and health culture, 2022)
The aim of the own research was to diagnose the influence of dance on the improvement of mental and social health on young people participating in the contemporary dance ensemble. The study included 46 people, aged 15–23, from the AGAT Contemporary Dance Group, operating at the Culture and Recreation Center in Strykow. Based on the diagnostic survey method and the survey technique, the impact of dance was assessed and its advantages were presented. The respondents positively evaluate dance as a form of physical activity, they willingly participate in dance classes. For them, dancing is a stepping stone from problems, the possibility of improving their physical fitness, acquiring motor skills, a source of self-realization, as well as the possibility to de-stress and an interesting form of spending free time. Thanks to the classes, the physical activity of the dancers is maintained at a high level, and their participation for many years in a team, it improves their physical and mental fitness, teaching skills that will be useful in everyday life. Being in a dance group is all about good memories and experiences. The dancers admit that from the perspective of the years of participation in a dance ensemble, their health remains at a good level.Dance brings many positive aspects to our lives and the lives of dancers. Thanks to it, we can improve our body at any age. The dancers, who are participants of the team, derive only good examples from the classes thanks to a passionate instructor who also acts as an educator. Dancing can be a great form of rest after a hard day, a form of relaxation or activities in your spare time. For children and teenagers, it can be an interesting form of extracurricular activities, and when they catch the bug, it can become a lifelong passion.